Training characteristics of paralympic swimmers - Fulton, S. K.; Pyne, D. B.; Hopkins, W. G.; Burkett, B. (The Journal of Strength and Conditioning Research, 2010)
The ability to monitor training is critical to the process of quantifying training periodization plans, yet weekly patterns of volume and intensity for Paralympic swimmers before competition have not been reported. Sixteen swimmers were monitored prospectively over a 16-week training block constituting 4 training phases (early, mid, late, and taper), before a World Championship. Training volume (total and main set distance) and intensity (percentage of peak heart rate [HR], swimming velocity, and rate of perceived exertion [RPE]) were quantified using an online training diary, and changes in training load were examined over the 4 training phases. For a subgroup of swimmers (n = 12), with similarities in underlying disability, change in performance between Selection Trials and World Championships was also quantified. Substantial increases in total training volume (29.6%) were observed late phase, and main set volume was reduced substantially (24.1%) during the taper phase. Small to moderate increases in training intensity (HR 2.4%, velocity 4.5%, and RPE 6.7%) were observed late phase and maintained through the taper. There were no clear associations between discrete training measures and competition performance. Swimmers competing at the Paralympic level seem to follow traditional periodized patterns of training, similar to those of swimmers at the Olympic level, before competition. Coaches of elite swimmers with a disability should review their prescribed patterns of training before major competition: A more substantial taper (larger reduction in volume) could elicit a greater improvement in performance. Training prescription should account for different disabilities and classes and individual circumstances of elite swimmers with a disability.